SPE Oklahoma City Oil and Gas Symposium 2019
DOI: 10.2118/195185-ms
|View full text |Cite
|
Sign up to set email alerts
|

Gas Huff and Puff Process in Eagle Ford Shale: Recovery Mechanism Study and Optimization

Abstract: US unconventional resource production has developed tremendously in the past decade. Currently, the unconventional operators are trying many strategies such as refracturing, infill drillings and well spacing optimization to improve recovery factor of primary production. They are also employing big data and machine learning to explore the existed production data and geology information to screen the sweet spot from geology point of view. However, current recovery factor of most unconventional reservoirs is stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Yu et al highlighted the importance of CO 2 diffusion coefficient measurements, because they may make a significant contribution to the total oil recovery. However, it is difficult to precisely measure it under laboratory conditions . Zhang et al concentrated on disclosing the mechanisms of gas-injection EOR through a combination of laboratory investigational findings, ternary diagram analysis, core-scale, and field-scale simulation.…”
Section: Gas-eor Mechanism In Shale/tight Reservoirsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu et al highlighted the importance of CO 2 diffusion coefficient measurements, because they may make a significant contribution to the total oil recovery. However, it is difficult to precisely measure it under laboratory conditions . Zhang et al concentrated on disclosing the mechanisms of gas-injection EOR through a combination of laboratory investigational findings, ternary diagram analysis, core-scale, and field-scale simulation.…”
Section: Gas-eor Mechanism In Shale/tight Reservoirsmentioning
confidence: 99%
“…However, it is difficult to precisely measure it under laboratory conditions. 113 Zhang et al 114 concentrated on disclosing the mechanisms of gas-injection EOR through a combination of laboratory investigational findings, ternary diagram analysis, core-scale, and field-scale simulation. The study confirmed that diffusion is the most important parameter in CO 2 injection EOR.…”
Section: Gas-eor Mechanism In Shale/tightmentioning
confidence: 99%
“…Various studies have been conducted on the gas recovery enhancement from tight gas reservoirs; however, there is no significant progress made, compared with conventional gas reservoirs [62][63][64][65][66][67]. Problems such as liquid injection difficulties for chemical enhanced recovery methods or mixture problems of injected gas with in situ gas have caused lower displacement efficiency [68][69][70][71][72][73]. Vo Thanh et al (2020) investigated the optimal WAG (alternating water gas) performances by a robust optimization workflow as an artificial intelligence optimizer in carbon dioxide sequestration processes for sandstone reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…According to Yu et al (2014), the most important parameters for CO 2 -based HnP are the CO 2 injection rate, injection time, number of cycles, and CO 2 diffusivity. Other parameters such as fracture conductivity, soaking time, permeability, and fracture half-length are less sensitive to incremental oil recovery.…”
Section: Introductionmentioning
confidence: 99%